Free oxygen ion activity in binary alkali silicate glasses - Pyare R.; Nath P. (My University, 2025)
Relative free oxygen ion activity (Δ log O2-) was empirically calculated for binary alkali silicate glasses at 1400°C. Excellent agreement was found between these values and with those obtained from data on solubility of water vapour in glasses. On plotting Δ log O2- against mol% alkali oxides, three different straight lines for lithium, sodium and potassium silicate glasses were obtained whose slopes were approximately inversely proportional to the Coulombic forces between non-bridging oxygens (O-) and alkali ions. Linear relationships were also found between log K′ (K′ = (mx+n)+)/(Mx+)(PO2n/4) and δ log O2- for Fe2+Fe3+, Ce3+Ce4+, As3+As5+, Sn2+Sn4+ and Cr3+Cr 6+ redox pairs in binary alkali silicate glasses. This clearly shows that at constant temperature and partial pressure of oxygen, the redox equilibria are mainly dictated by free oxygen ion activity in binary alkali silicate glasses. It is predicted that there would be approximately a linear relationship between log K′ and Δ log O2- for any redox pair for binary alkali silicate glasses in the concentration range 20-40 mol% alkali oxides. This linear relation opens up a new possibility of predicting the concentrations of redox ions present in lower and higher valence states in any binary alkali silicate glasses containing alkali oxides between 20 and 40 mol% if the values of log K′ are known for two or three glasses in the above system. © 1991.